2008
DOI: 10.1097/mca.0b013e32830d27d2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of fluvastatin therapy on plasma interleukin-10 levels in patients with chronic heart failure

Abstract: Fluvastatin therapy might lead to an increase in plasma IL-10 levels and an associated improvement in vagal tonus as assessed by HRR at 1 min in patients with HF. These findings might partly explain the possible benefit observed in statin trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In 35 (83%) studies, patients had a diagnosis of type 2 diabetes, in five (12%), patients had a diagnosis of type 1 or 2 diabetes, 55 70 71 79 80 and in two (5%) studies, patients had a diagnosis of type 1 diabetes only. 63 74 Of the 22 (49%) studies that reported the average length of the diagnosis of diabetes, the median was 8 years (range 4-11, interquartile range 7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 35 (83%) studies, patients had a diagnosis of type 2 diabetes, in five (12%), patients had a diagnosis of type 1 or 2 diabetes, 55 70 71 79 80 and in two (5%) studies, patients had a diagnosis of type 1 diabetes only. 63 74 Of the 22 (49%) studies that reported the average length of the diagnosis of diabetes, the median was 8 years (range 4-11, interquartile range 7).…”
Section: Resultsmentioning
confidence: 99%
“…Hence to investigate the role of baseline scores, an individual patient data meta-analysis would be required. We tried contacting the authors for their baseline data, but only three responded 387380. We recommend that these data are reported in future trials to allow the adjusted baseline change scores to be used instead of the final scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of IL-10 was shown to be elevated in the plasma of unstable angina patients using statins [20]. Studies with heart failure patients also supported the elevation of IL-10 with statin usage [21]. While IL-10 shows inhibitory features on MMPs, enzyme myeloperoxidase can oxidatively activate MMP-8 and MMP-9 and contributes to the periodontal destruction and can generate reactive oxygen species [22].…”
Section: Introductionmentioning
confidence: 92%